Effect of Educational Program on Nurses' Performance Regarding Prevention and Management of Intravenous Extravasation Chemotherapy - Nehal M. Abo El-Fadl (Evidence-Based Nursing Research)
Context: Systemic chemotherapy plays a pivotal role in curative therapy for patients with hematological neoplasms and several types of advanced solid tumors. Extravasation describes an anticancer agent's accidental leakage from a vessel into the surrounding tissues, leading to irreversible local injuries and severe disability. Despite its considerable clinical importance, evidence-based information on extravasation in chemotherapy is lacking.